Does the transition into daylight saving time affect students' performance? - Stefanie P. Herber; Johanna Sophie Quis; Guido Heineck (Bamberg University, Bamberg Economic Research Group (BERG), 2015)
We use international student assessment data on more than 22,000 students from six European countries and a regression discontinuity design to investigate whether the transition into daylight saving time (DST) affects elementary students' test performance in the week after the time change. We do not find reliable statistical effects on students' performance, neither in math, science nor reading. Our results therefore challenge the prevailing public opinion that DST should be abandoned because of its detrimental effects on school children's performance.
Keywords: D04; H41; I20; I29; 330; Daylight saving time; school achievement tests; cognitive performance; natural experiment; regression discontinuity design; TIMSS; PIRLS